Spectrophotometric Determination of Ranitidine-HCl in Pure Form and Pharmaceutical Formulations with Metol and potassium hexacyanoferrate (ΙΙΙ) - Abeer Qays Abdulwahab (University of Thi-Qar Journal of Science, 2019)
A simple, sensitive and accurate spectrophotometric method of determination of Ranitidine-HCl (RNH) in pureform and its pharmaceutical formulation. Was used in this studyThe method is based on the formation of (RNH)complex. The reaction between the Ranitidine-HCl with the mixture of metol and potassium hexacyanoferrate (ΙΙΙ) wasevaluate metol ( Nmethyl – p - aminophenosulphate ) for the spectrophotometric determination of the Ranitidine -HCl . The maximum absorbance of the colored complex occurred at λ = 540nm. Reaction conditions have beenoptimized to obtain (RNH) complex of high sensitivity and longer stability. Under optimum conditions the absorbanceof the (RNH) complex where found to increase linearly with the increase in concentration of the Ranitidine-HCl whichcorroborated with correlation coefficient value. Of 0.09995with concetration ranges of(2-90) μg /ml relative standarddeviation and relative error of prediction for drug were lower . The proposed method was successfully applied todetermine of the selected Ranitidine-HCl in pure form and pharmaceutical formulations with good precision andaccuracy compared to standard method as revealed by t- and F- values , the results obtained agree well with the labeledcontents.